War in peace : an analysis of warfare since 1945 - Thompson, Robert, Sir, 1916-1992. (London : Orbis, 1981)
A review of the wars that have occured since 1945 from Malaya to the Gulf War from the Greek civil war to the Algerian revolution.
Includes bibliographical references (pages 308-309) and index.
Keywords: 1900-1999; Military art and science -- History -- 20th century; Military history, Modern -- 20th century; Military art and science; Military history, Modern; History